Raw Material Characterization And Reductive Leaching Of Low Grade Manganese Ore With Bamboo Sawdust In Sulphuric Acid - Muthalib, Nurhidayah Abdul (2019)
This research used two types of raw materials which are synthetic manganese ore and low grade manganese ore. The characterization analysis of raw materials was determined via morphological study and phase identification. The results showed synthetic manganese ore is high grade with 34.32 % Mn and the manganese ore is of low grade with 15.26 % Mn. The phase present in synthetic manganese ore is pyrolusite and the low grade manganese ore contains the pyrolusite, goethite and quartz phases. The reductive leaching of synthetic manganese ore and low grade manganese ore were conducted using bamboo sawdust as a reducing agent in sulphuric acid. Synthetic manganese ore was leached acted as a control experiment for the manganese ore. Leaching was conducted for 360 minute. Maximum manganese extraction and the effects of sulphuric acid concentration (2.5 M – 4.0 M) and temperature (70 oC – 100 oC) on manganese extraction were also determined. The results indicated maximum manganese extractions of 96.14 % and 75.48 % were achieved using 4.0 M sulphuric acid concentration at 100 oC for the synthetic manganese ore and low grade manganese ore. The sugar identification of bamboo sawdust and glucose degradation was also determined. Bamboo sawdust which contain cellulose (56.11 %) and hemicellulose (28.6 %) was degraded into glucose as the major sugar. The glucose present in the leaching system was (15-20) %. The glucose produced was used to reduce the Mn ores and degraded into organic acid. The major organic acid formed was formic acid (<0.005 ppm).